PENEGAKAN HUKUM BAGI PENGEMUDI KENDARAAN BERMOTOR DI BAWAH UMUR TANPA SURAT IZIN MENGEMUDI DITINJAU DARI UU NO. 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DIWILAYAH SURABAYA PUSAT - Muchammad Eko Pramono; Tuti Herningtyas (JOURNAL OF LAW AND NATION, 2023)
The purpose of this study is to discuss and analyze law enforcement for underage motorized vehicle drivers without a Driver's License based on Law Number 22 of 2009 concerning Road Traffic and Transportation in the Central Surabaya area as well as discuss and analyze obstacles in law enforcement for underage motorized vehicle drivers without a Driver's License based on Law Number 22 of 2009 concerning Traffic and Road Transport in Central Surabaya area. This research is included in normative juridical research. The results showed that law enforcement for underage motorized vehicle drivers without a Driver's License based on Law Number 22 of 2009 concerning Traffic and Road Transportation in the central Surabaya area was carried out with several efforts, namely: a) Provide an explanation that traffic regulations are important; b) Conduct traffic raids; c) Provide information or socialization.; and d) Increased technical traffic activity in the form of road repairs, or traffic signs and systems that control traffic flow. The results also showed that obstacles in law enforcement for underage motorized vehicle drivers without a Driver's License based on Law Number 22 of 2009 concerning Road Traffic and Transportation in the central Surabaya area include: limited persnonil and number of vehicles to patrol, lack of funds for operational activities, lack of socialization and public awareness about traffic signs